2016
DOI: 10.18632/oncotarget.11928
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of miR-29a in pancreatic cancer autophagy and its therapeutic potential

Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) is a highly lethal malignancy that responds poorly to current therapeutic modalities. In an effort to develop novel therapeutic strategies, we found downregulation of miR-29 in pancreatic cancer cells, and overexpression of miR-29a sensitized chemotherapeutic resistant pancreatic cancer cells to gemcitabine, reduced cancer cell viability, and increased cytotoxicity. Furthermore, miR-29a blocked autophagy flux, as evidenced by an accumulation of autophagosomes and autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 89 publications
(103 reference statements)
2
62
0
Order By: Relevance
“…MicroRNAs are small noncoding RNAs severing as important post‐transcriptional regulators of gene expression, and their abnormal expression has been shown to contribute to tumorigenesis . MiR‐29a has been recognized as a critical tumor suppressor and downregulated in several different types of solid tumor tissues, including PC . Our findings indicated that DRP1 is a novel target of miR‐29a in PC cells, and introduction of synthetic miR‐29a significantly attenuated both the growth and metastasis promoted by DRP1 overexpression in PC cells, suggesting that downregulated miR‐29a may contribute to the upregulation of DRP1 and thus tumor growth and metastasis in PC cells.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…MicroRNAs are small noncoding RNAs severing as important post‐transcriptional regulators of gene expression, and their abnormal expression has been shown to contribute to tumorigenesis . MiR‐29a has been recognized as a critical tumor suppressor and downregulated in several different types of solid tumor tissues, including PC . Our findings indicated that DRP1 is a novel target of miR‐29a in PC cells, and introduction of synthetic miR‐29a significantly attenuated both the growth and metastasis promoted by DRP1 overexpression in PC cells, suggesting that downregulated miR‐29a may contribute to the upregulation of DRP1 and thus tumor growth and metastasis in PC cells.…”
Section: Discussionmentioning
confidence: 65%
“…MicroRNAs are small noncoding RNAs that serve as important post‐transcriptional regulators of gene expression. MiR‐29a has been proved as a frequently downregulated tumor suppressor in various types of cancers, including PC . Because of several previous studies that have revealed DRP1 as a novel target of miR‐29a, we thus hypothesized that downregulated miR‐29a could be involved in the overexpression of DRP1 in PC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, miR-21, miR-31-3p, miR-203, miR-16 were up-regulated which were found to be engaged in regulating apoptosis (miR-21) [31], migration and invasion (miR-31 and miR-203) [32,33], and diagnosis(miR-16) [34] of pancreatic cancer. On the other hand, miR-210-3p, miR-29a, miR-125b, miR-133a were down-regulated, they have been reported to be associated with pancreatic cancer such as regulating cells interaction (miR-210) [35], as an autophagy inhibitor (miR-29a) [36], as a tumor suppressor(miR-125b and miR-133a) [36]. However, none of the miRNAs above is well characterized in PCSCs.…”
Section: Panc-1 Spheroid Cells Have Higher Tumorigenic Potential In Vivomentioning
confidence: 99%
“…17 Interestingly, Ap1/Ets-1 binding region plays a central function in transforming growth factor betamediated the regulation of miR-29. 18 Given that restoring miR-29a expression has been demonstrated to repress the development and aggravation of malignant tumors, 6,15 miR-29a, as a potent therapeutic agent target, is considered to be applied in hepatocellular therapies. 19 SEVO commonly emerged as an anesthetic for subjects.…”
Section: Discussionmentioning
confidence: 99%